PERAN DAN KETERLIBATAN GEREJA TERHADAP MASYARAKAT MISKIN ERA MODERN - Sainyakit, Andreas; Solilit, Fidelis; Rahae, Philipus (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STPAK St. Yohanes Penginjil Ambon, 2023)
Poverty is the part of life and no one can deny it. In fact, it brings a lot of people to helplessness and discouragement. It causes people to suffer physically and psychologically. People run into the poverty due to the crisis of economic, injustice, extortion, and the existence of social strata (social class). It comes as well to the life of society because of a government system that is not in favor of the community. Poverty is not the new thing of our society. It has become a classic problem experienced by every nation, especially Indonesia. Until now poverty brings a major problem for this nation and it still cannot completely be resolved.Poverty is social and economic problem concerned by Chatolic Church. She is called dan sent to fight for the fairness for the poor. The Church is the voice of the voiceless to help the poor to reach out their better life. She proclaims“option for the poor”as the main mission that should be fought for prosperity and salvation of the people. Therefore, she reminds and encourages all people in society, especially local and national government in order to pay attention to the poor. Economic empowerment of society is one of the most building program that can be realized by both the Church and government to save life of the poor. Key word: Poverty, poor, service of the Church, economic empowerment.